BRANDING MANAGEMENT OF HIGHER EDUCATION INSTITUTIONS OF UKRAINE IN THE CONTEXT OF INTEGRATION INTO THE WORLD EDUCATIONAL SPACE - Kolisnichenko , Natalia (Pressing Problems of Public Administration, 2021)
The paper explores the principles of branding of higher education institutions of Ukraine in the context of integration into the world educational space. It defines the categories “brand”, “branding” in higher education. It is proved that the brand is different from the trademark. The paper reveals “rational” and “emotional” components of the brand.The concept of “brand” is considered as a rather complicated complex of socio-economic, socio-ethical and psychological relationships between producers and consumers of goods and services.The target of the paper is University branding. Today it is a relevant topic: consulting firms offer specialized branding and marketing services to universities, and branding associations create their own units on the territory of a campus. Branding management in higher education provides the following: formalization of branding at higher education institutions; commercialization (transition to market mechanisms); promoting of branding activities at higher education institutions; professionalization of Universities branding.The paper identifies three branding trends at universities in the world:– first, many universities have restyled their representative symbol. The traditional emblems, which were the signals of the profession, are restyled into a logo, which can be easily mistaken for a commercial brand;– the second trend is for universities to add to, rather than replace their traditional emblem. In this trend, new symbols serve different purposes;– the third trend is for universities to establish claims to their symbols by protecting these as intellectual properties.The brand of a higher education institution:– first, realizes the emotional image formed by the marketing communications and determines the rational perceptions of the consumer regarding the quality, characteristics, reputation, and benefits obtained as a result of his/her personal perception of the brand;– secondly, it stimulates strategic management of the educational institution with regard to its mission, goals and positioning;– thirdly, it is a tool for profit, an element of intellectual property.The paper reveals three levels of brand “value” formation: the first level refers to the social value of the brand; the second - to the consumer value of the brand; the third level is a long-lasting brand value.The further research can be conducted within the analysis of the peculiarities of brand management and the concept of brand leadership of state and private higher education institutions.